EFFECT OF SKILLS ENHANCEMENT PROGRAM ON TEACHERS’ PERFORMANCE IN ASINGE SECONDARY SCHOO, TORORO DISTRICT - ALUKUDO NAOME BEATRICE (My University, 2024)
ABSTRACT The study determined the effect of skills enhancement program on teachers’ performance in Asinge Secondary School, Tororo District. The study was guided by research objectives which included examining the influence of on-job training on teachers’ performance, finding out the influence of off-job training on teachers’ performance and finding out the challenges teachers face in the performance of their duties in Tororo District Local Government. The study employed both primary and secondary collection method covering a study population of 75 but concentrated on a sample of 63 respondents who were purposely selected and simple random sampling were used to minimised biased results. Self administerd questionares and interview guide were the main research intruments of the study. Data collected was analyzed using SPSS package which included the frequencies table,correlation, regression model and ANOVA. The findings revealed that the knowledge and skills presented during mentorship are directly related to my job requirements, mentoring increases my confidence at the work place, and mentoring is part of the learning culture at our local government. In addition, workshops allow employees to actively participate in sharing powerful information at local government, workshops create for employee an effective learning opportunity, and the knowledge and skills i acquire from workshops are relevant to my job. Besides, the findings showed that Asinge Secondary School, Tororo District organizes trainings to enhance employee performance, retreats help employees to overcome fears, and stimulate me to work toward a shared goal at Mbale Municipal Council. Conclusively, the researcher found out that Asinge Secondary School, Tororo District offer training to its non-teaching staff in form of off-job training, on-job training and mentorship which resulted into accomplishment of tasks in time, minimized organizational turn-over, good working relationship with the public, and harmony among staff. The researcher recommends that the authorities need to continue to train its staff, carry out mentorship programs, encourage team work, motivation and carry out training across all departments.